Allylation and heterocycloaddition reactions of aldimines: Furan- and quinolinecarboxaldehydes - Kouznetsov, V; Ocal, N; Turgut, Z; Zubkov, F; Kaban, S; Varlamov, AV (SPRINGER-VERLAG WIEN, 1998)
New derivatives of alpha-substituted furans were prepared in high yields from easily available alpha-furfurylidenbenzilamines via nucleophilic C-allylation. The homoallylamines obtained this way were used for the synthesis of some polyfunctional aminobutene derivatives. In addition, 4-thiazolidinones some of which are hetaryl substituted at the 2-position were prepared by the reaction of mercapto acids with quinoline carboxaldehydes and p-phenetidine. All new products were fully characterized.
Keywords: Diels-Alder adduct; alpha-furfurylidenbenzilamine; nitrone; alpha-substituted furan; 4-thiazolidinone; Chemistry